2021
DOI: 10.1002/fsn3.2254
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin could alleviate liver injury caused by Maillard reaction products with furan ring through regulating necroptosis pathway

Abstract: As classical MRPs, the toxic effects of furosine, pyralline, and 5‐hydroxymethylfurfural (5‐HMF) in liver tissue are evaluated and the related mechanism is investigated here, and the protective effects of lactoferrin on liver injury caused by Maillard reaction products (MRPs) with furan ring are proved in vitro and in vivo. First, we detect the concentrations of furosine, pyralline, and 5‐HMF in several foods using ultrahigh‐performance liquid chromatography (UHPLC). Then, the effects of the three MRPs on live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…These results are consistent with some previous report investigations which reported that the serum level of AGEs are significantly higher in DM patients as compared with the control group (Wang et al, 2019, Sun et al, 2020, Ramasamy et al, 2016. Recently a similar pattern of data has been obtained, about a significant increase in CML, CEL, and Pyralline serum levels in DM patients (Nakano et al, 2020, El Jellas et al, 2022, Fan et al, 2021. Based on our data, we hypothesize that persistent hyperglycemia increases the generation of reactive oxygen species (ROS) from a variety of sources in diabetic individuals.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with some previous report investigations which reported that the serum level of AGEs are significantly higher in DM patients as compared with the control group (Wang et al, 2019, Sun et al, 2020, Ramasamy et al, 2016. Recently a similar pattern of data has been obtained, about a significant increase in CML, CEL, and Pyralline serum levels in DM patients (Nakano et al, 2020, El Jellas et al, 2022, Fan et al, 2021. Based on our data, we hypothesize that persistent hyperglycemia increases the generation of reactive oxygen species (ROS) from a variety of sources in diabetic individuals.…”
Section: Resultssupporting
confidence: 93%